Effect of proteins isolated from Brazilian snakes on enterovirus A71 replication cycle: An approach against hand, foot and mouth disease - Shimizu, Jacqueline Farinha [UNESP]; Feferbaum-Leite, Shiraz; Santos, Igor Andrade; Martins, Daniel Oliveira Silva [UNESP]; Kingston, Natalie J.; Shegdar, Mona; Zothner, Carsten; Sampaio, Suely Vilela; Harris, Mark; Stonehouse, Nicola J.; Jardim, Ana Carolina Gomes [UNESP] (Elsevier, 2023)
Enterovirus A71 (EVA71) belongs to the Picornaviridae family and is the main etiological agent of hand, foot, and mouth disease (HFMD). There is no approved antiviral against EVA71, and therefore the search for novel anti-EVA71 therapeutics is essential. In this context, the antiviral activity of proteins isolated from snake venoms has been reported against a range of viruses. Here, the proteins CM10 and CM14 isolated from Bothrops moojeni, and Crotamin and PLA2CB isolated from Crotalus durissus terrificus were investigated for their antiviral activity against EVA71 infection. CM14 and Crotamin possessed a selective index (SI) of 170.8 and 120.4, respectively, while CM10 and PLA2CB had an SI of 67.4 and 12.5, respectively. CM14 inhibited all steps of viral replication (protective effect: 76 %; virucidal: 99 %; and post-entry: 99 %). Similarly, Crotamin inhibited up to 99 % of three steps. In contrast, CM10 and PLA2CB impaired one or two steps of EVA71 replication, respectively. Further dose-response assays using increasing titres of EVA71 were performed and CM14 and Crotamin retained functionality with high concentrations of EVA71 (up to 1000 TCID50). These data demonstrate that proteins isolated from snake venom are potent inhibitors of EVA71 and could be used as scaffolds for future development of novel antivirals.
Keywords: Antiviral; Brazilian snakes; Enterovirus A71; EVA71; Toxins